The Republic of the Living : Biopolitics and the Critique of Civil Society - Vatter, Miguel (Book collections on Project MUSE., 2014)
The aim of this book is to explain what makes the contemporary discourse of biopolitics essential both to the understanding and to the critique of modern civil society, as developed from Hegel and Marx up to Arendt, Foucault and Agamben. The book seeks to identify the affirmative political potential found in the biopolitical category of natality, and its relation to both normality and normativity, within and between each sphere of civil society.